The Church as the new family of God - Rabczyński, Paweł (Array, 2021)
Jesus founded His Church as the new family of God by instituting the Twelve. The new family is a real space which fulfils the Kingdom of God. It is a community of Jesus’ disciples which fosters the rule of God in the world and has an explicitly institutional dimension. The founding of the new family fulfils the promise to create the new Israel made in the Old Testament. The ethos of the new family of God is aimed at proclaiming the universal reign of God, as it is the mission bestowed on the family by Jesus. Its moral principles were laid out in the Sermon on the Mount. The new family of God is a space where all the promises made by God to Israel come to fulfilment. In this sense, we can speak of continuity between the nation of Israel and the Ecclesia. The Church does not replace the people of the Old Testament but is a continuation thereof in Jesus Christ.